2015
DOI: 10.2527/jas.2015-9220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating equations estimating change in swine feed intake during heat and cold stress1

Abstract: ABSTRACT:The objectives of this study were to evaluate heat stress feed intake models for growing swine using a data set assembled from the literature and to develop a series of new equations modeling the influence of the thermal environment and interactions between the thermal environmental and other factors on feed intake. A literature survey was conducted to identify studies assessing intake responses to temperature. The resulting data set comprised 35 studies containing 120 comparisons to thermoneutral int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…The weighting factor was calculated by dividing the reciprocal SEM by the mean reciprocal SEM within analysis type. Dividing by the mean reciprocal SEM normalized the weighting factors to 1 irrespective of analysis type, effectively standardizing the weights across fixed effect or mixed models (White et al, 2015;Roman-Garcia et al, 2016). In studies that reported SEM as less than one-fourth the mean SEM, the SEM was set to one-fourth of the mean SEM across all studies to prevent over weighting (Firkins et al, 2001;Roman-Garcia et al, 2016;White et al, 2016).…”
Section: Weighting Strategiesmentioning
confidence: 99%
“…The weighting factor was calculated by dividing the reciprocal SEM by the mean reciprocal SEM within analysis type. Dividing by the mean reciprocal SEM normalized the weighting factors to 1 irrespective of analysis type, effectively standardizing the weights across fixed effect or mixed models (White et al, 2015;Roman-Garcia et al, 2016). In studies that reported SEM as less than one-fourth the mean SEM, the SEM was set to one-fourth of the mean SEM across all studies to prevent over weighting (Firkins et al, 2001;Roman-Garcia et al, 2016;White et al, 2016).…”
Section: Weighting Strategiesmentioning
confidence: 99%
“…The present study found that sows mated within 6 days after weaning had higher effects of heat stress on farrowing rate than the other sows. Under heat conditions, sows are not able to have enough feed intake during lactation to maintain their body condition (Koketsu, Dial, Pettigrew, Marsh, & King, ; White, Miller, & Hanigan, ), and thus their body condition at weaning could be poorer than usual. Sows mated after 7 days have a time to recover their condition from weaning to service, whereas sows mated within 6 days after weaning did not have enough time to recover their condition.…”
Section: Discussionmentioning
confidence: 99%
“…A quadratic response to temperature was employed because animals likely have some physical maximum intake due to digestive tract space limitations and at extremely high temperatures, animals stop eating altogether. An initial comparison of linear and quadratic temperature models suggested lower RMSPE and higher CCC for the quadratic fit (White et al in press). The residuals of the quadratic model were assessed against additional explanatory variables available within the data set.…”
Section: Methodsmentioning
confidence: 99%